5,10-Methylenetetrahydrofolate Reductase Deficiency and Myoclonic Epilepsy - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from the Children's Hospital of Philadelphia, PA, and McGill University, Montreal, Quebec, CA, report an adolescent learning-disabled girl who presented at age 14 years with an epilepsy syndrome initially diagnosed as juvenile myoclonic epilepsy.